Deficiency of Mettl3 in Bladder Cancer Stem Cells Inhibits Bladder Cancer Progression and Angiogenesis - Wang, Ganping; Dai, Yarong; Li, Kang; Cheng, Maosheng; Xiong, Gan; Wang, Xiaochen; Chen, Shuang; Chen, Zhi; Chen, Jianwen; Xu, Xiuyun; Ling, Rong-song; Peng, Liang; et al. (Frontiers in Cell and Developmental Biology, 2021)
RNA N6-methyladenosine is a key step of posttranscriptional modulation that is involved in governing gene expression. The m6A modification catalyzed by Mettl3 has been widely recognized as a critical epigenetic regulation process for tumorigenic properties in various cancer cell lines, including bladder cancer. However, the in vivo function of Mettl3 in bladder cancer remains largely unknown. In our study, we found that ablation of Mettl3 in bladder urothelial attenuates the oncogenesis and tumor angiogenesis of bladder cancer using transgenic mouse model. In addition, conditional knockout of Mettl3 in K14+ bladder cancer stem cell population leads to inhibition of bladder cancer progression. Coupled with the global transcriptome sequencing and methylated RNA immunoprecipitation sequencing results, we showed that deletion of Mettl3 leads to the suppression of tyrosine kinase endothelial (TEK) and vascular endothelial growth factor A (VEGF-A) through reduced abundance of m6A peaks on a specific region. In addition, the depletion of Mettl3 results in the decrease in both messenger RNA (mRNA) and protein levels of TEK and VEGF-A in vitro. Taken together, Mettl3-mediated m6A modification is required for the activation of TEK–VEGF-A-mediated tumor progression and angiogenesis. Our findings may provide theoretical basis for bladder cancer treatment targeting Mettl3.